Attitude toward m-advertising and m-repurchase - Nadia Jiménez; Sonia San-Martín (European Research on Management and Business Economics (ERMBE), 2017)
One of the business models that attracts scholars and professionals' interest is mobile commerce. This paper applies the theory of shopping preference to this field. It analyzes the role of personal factors (perceived control and propensity to use technology), social factors (influence of a social group), and epistemic factors (compatibility) to determine consumers' attitude toward mobile advertising (madvertising) and mobile repurchase (m-repurchase). The information of 973 mobile shoppers is analyzed in two contexts (Spain as a developed country and Mexico as a developing country). A positive attitude toward m-advertising is confirmed to increase m-repurchase through the mobile phone and the indirect influence of personal, social, and epistemic factors on shoppers m-repurchase (through the attitude toward m-advertising) varies depending on the analyzed market.
Keywords: M3; 650; Attitude; Mobile; M-repurchase